Traits and needs as predictors of life satisfaction: a behavioral genetics perspective - Bratko, Denis; Butković, Ana; Vukasović Hlupić, Tena (2014)
The aim of this study was to: i) explore heritability of personality traits, psychological needs and life satisfaction in Croatian population using the twin design ; ii) to compare trait vs. need theoretical perspective regarding their predictive validity of life satisfaction ; and iii) to compare trait vs. need theoretical perspective using behavioral genetic multivariate design. The sample consisted of 339 twin pairs (105 MZ and 234 DZ), aged between 15 and 22. Personality traits were organized using Five Factor Model framework while psychological needs were organized using Self-Determination Theory. Results indicate that life satisfaction is highly heritable in Croatian population. On the phenotypic level both personality traits and psychological needs predicted life satisfaction. Genetic variance of life satisfaction overlaps with both personality and psychological needs, while environmental variance overlap seems to be higher with basic needs than with personality traits.
Projekt MZOS
Projekt MZOS
ENG